Introduction of Meglumine Diatrizoate into the Middle Cranial Fossa: A Rare Fatal Complication of Temporomandibular Joint Arthrography. Issue 7 (October 2018) - Li, Wei; Wei, Lili; Wang, Fang; Cheng, Yong; Li, Bo
Abstract : Abstract: The authors here report a rare fatal complication of temporomandibular joint (TMJ) arthrography. A 57-year-old woman suddenly exhibited spasm and dizziness during TMJ arthrography. A multislice CT scanning of head demonstrated a defect in the roof of the glenoid fossa and unanticipated introduction of meglumine diatrizoate into the middle cranial fossa, which should account for neurotoxic symptoms of the patient and could be fatal if not appropriately treated in time. As TMJ puncture is widely performed in clinical practice and generally considered a safe technique, this case might serve as a reminder of the potential risk of the anatomical variation—a defect in the roof of the glenoid fossa—to TMJ clinical practitioners.